Defense against oxidative stress in Caenorhabditis elegans by dark tea - Wang, Jianxiu; Zhang, Kaiheng; Zhang, Yaya; Ge, Shumin; Zhang, Shuhua (Frontiers in Veterinary Science, 2024)
Dark tea, rich in nutricines including tea polyphenols and free amino acids, is a kind of post-fermented tea. The potential application of nutricines against oxidative damage and senescence, which drives animal health maintenance and disease prevention, has attracted considerable interest. In this study, the effect of dark tea and its effects on longevity and defense against oxidative stress was investigated in the Caenorhabditis elegans (C. elegans) model. Under normal conditions, dark tea extended the lifespan without significant impairment of propagation. It also improved the motility, alleviated the fat accumulation and apoptosis. Additionally, orally administered dark tea could significantly decrease the level of reactive oxygen species (ROS) and resulted in a superior lifespan in H2O2-induced oxidative stressed C. elegans. In antioxidant assays in vitro, dark tea was found to be rich in strong hydroxyl, DPPH and ABTS+ free radical scavenging capacity. Interestingly, mRNA sequence analyses further revealed that dark tea may catalyze intracellular relevant oxidative substrates and synthesize antioxidants through synthetic and metabolic pathways. These results suggest that dark tea is worth further exploration as a potential dietary supplement for the maintenance of animal health and the prevention of related diseases.